Biomass production and allocation in Jatropha curcas L. seedlings under different levels of drought stress - Achten, W.M.J.; Maes, W.H.; Reubens, B.; Mathijs, E.; Singh, Virendra Pal; Verchot, Louis V.; Muys, B. (2010)
In a greenhouse experiment we applied three levels of drought stress and monitored growth variables and biomass production of Jatropha curcas seedlings propagated from three seed accessions. We determined biomass allocation, allometric relationships and plant traits. Well-watered J. curcas seedlings grew 0.81 ± 0.15 cm day-1 in length and produced 1.49 ± 0.31 g dry biomass day-1. Under medium stress (40% plant available water) the plants maintained a similar stem shape, although they grew at lower rate (stem length: 0.28 ± 0.11 cm day-1; dry biomass production: 0.64 ± 0.18 g day-1). Seedlings under extreme drought stress (no irrigation) stopped growing, started shedding leaves and showed shrinking stem diameter from the 12th day after the start of the drought treatment. The drought treatment did not influence the wood density (0.26 g cm-3). The root/shoot ratio of the wet treatment was 0.27, which is low compared to other tropical trees. Both the biomass allocation and root/shoot were significantly influenced by drought. Plants of the different accessions were uniform in biomass production and plant traits. The allometric relationship predicting total aboveground biomass (B) with the stem diameter (D) (B = 0.029 × D2.33; R2 = 0.89) fits well in universal scaling models in which the exponent is expected to converge to 2.67 at plant maturity. Based on a small validation data set from mature J. curcas individuals this hypothesis could be confirmed. A second regression model predicts the total leaf area (LA) as a function of stem diameter (LA = 2.03 × D2.41; R2 = 0.95). The estimated transpiration crop coefficient Kcb ranged from 0.51 to 0.60 for the well-watered plants.